Sengkarut Pola Hubungan Lembaga Penyelenggara Pemilu di Daerah Otonomi Khusus - Mutiara Fahmi; Zahlul Pasha; Khairil Akbar (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
This article seeks to analize the pattern of relations and authority of election agencies in special autonomous regions in Indonesia. The difference in the pattern of relations between election agencies in the special sutonomy region coincided with the implementation of asymmetric decentralization policies in Indonesia. As a result, differences in authority and specificity that is owned by one region with other regions. Whereas the Indonesian constitution based on Article 22E paragraph (5) of the 1945 Constitution of the Republic of Indonesia states that all regulations relating to the electoral institutions in Indonesia apply nationally. The research method used is normative and empirical. This study found similarities and differences in the pattern of relationships and authority of election agencies in the special sutonomy Region. The similarity is that the election agencies in this Special Autonomous Region has lost certain duties and authorities that affect the pattern of their relationship. The difference lies in the lost duties and authority. In DKI Jakarta, the duties and responsibilities of the election organizers in the Regency/City are only in the context of assisting the Election organizing tasks in the Province. The duties and authority of the election organizers in DIY are reduced in the case of the Governor General Election. While in Aceh, the task of supervision is divided between two organizing agencies, namely the Aceh Panwaslih and the Aceh Province Panwaslih. In the future, this pattern of relations and authority will become a source of conflict and dispute. While in Papua Province, the election organize did not hold general elections due to the implementation of the noken system in some of these areas. Artikel ini berupaya menganalisis pola hubungan lembaga penyelenggara pemilu di daerah otonomi khusus di Indonesia. Perbedaan pola hubungan lembaga penyelenggara pemilu di daerah otsus muncul bersamaan dengan implementasi kebijakan desentralisasi asimetris di Indonesia. Akibatnya, muncul perbedaan kewenangan dan kekhususan yang dimiliki oleh satu daerah dengan daerah lain. Padahal konstitusi Indonesia berdasarkan Pasal 22E ayat (5) UUD NRI 1945 menyebutkan bahwa segala peraturan yang terkait dengan lembaga pemilihan umum di Indonesia berlaku secara nasional. Metode penelitian yang digunakan adalah normatif dan empiris. Penelitian ini menemukan adanya kesamaan dan perbedaan pola hubungan dan kewenangan lembaga penyelenggara Pemilu di Daerah Otonomi Khusus. Kesamaannya adalah, lembaga penyelenggara Pemilu di Daerah Otonomi Khusus ini sama-sama kehilangan tugas dan kewenangan tertentu yang memengaruhi pola hubungan mereka. Perbedaannya terletak pada tugas dan kewenangan yang hilang. Di DKI Jakarta, tugas dan kewengan penyelenggara Pemilu di Kabupaten/Kota hanya dalam rangka membantu tugas penyelenggara Pemilu di Provinsi. Tugas dan kewenangan penyelenggara Pemilu di DIY diciutkan dalam hal Pemilukada Gubernur. Sedang di Aceh, tugas pengawasan dibagi kepada dua lembaga penyelenggara, yakni Panwaslih Aceh dan Panwaslih Provinsi Aceh. Ke depan, pola hubungan dan kewenangan ini menjadi sumber konflik dan sengketa. Sementara di Provinsi Papua, lembaga penyelenggara pemilu tidak melaksanakan pemilihan umum akibat penerapan sistem noken di beberapa daerah tersebut.